Mothers' Grief Experiences of Losing Their Only Child in the 2008 Sichuan Earthquake: A Qualitative Longitudinal Study. (May 2020) - Fu, Fang; Chen, Lin; Sha, Wei; Chan, Cecilia L. W.; Chow, Amy Y. M.; Lou, Vivian W. Q.
The purpose of this study is to explore bereaved mothers' 2-year experiences of losing their only child in the 2008 Sichuan earthquake. Taking an interpretative phenomenological approach, this study interviewed six bereaved mothers four times (6 months, 12 months, 18 months, and 24 months) in Dujiangyan area in Sichuan Province. The findings suggest that these mothers' personal grief experiences evolved: initially, anger toward the cause of their children's deaths, following despair of meaningless life, guilt and regret, and finally yearning. Although their yearning and missing ebbed after 2 years, these mothers still had unresolved grief. These mothers also faced strained marital relationships and additional pressure from social interactions. This study illuminates that these mothers' personal grief experiences and their coping strategies corresponded to Chinese family and sociocultural context.